Is It Reasonable? Reasonable and Unreasonable Accommodations for Occupational Therapy Students in Clinical Settings - Rebecca Ozelie; Jennifer Bock; Sarah Gervais; Leah Schneider; Caitlyn Silhavy (Scholarworks @ WMU, 2022)
Despite the growing number of graduate students with disabilities, little is known about what accommodations are considered reasonable in various occupational therapy fieldwork settings. This study explores which accommodations fieldwork educators perceive as reasonable or unreasonable for occupational therapy students with disabilities. Snowball sampling methodology was used to distribute a virtual survey, using a descriptive design. One hundred and sixty-two occupational therapists and occupational therapy assistants answered questions relating to demographic information, clinical experience supervising fieldwork students, and their clinical judgement regarding commonly requested accommodations. Using a quantitative approach, the accommodations deemed most reasonable were allowing the use of adaptive equipment (n = 156, reasonable: 96.3%) and permission to excuse oneself from the unit to maintain health (n = 152, reasonable: 93.83%). The accommodations considered the most unreasonable were the use of an intermediary to perform physical tasks (n = 82, unreasonable: 50.62%) and the use of an American Sign Language interpreter (n = 42, unreasonable: 24.93%). Clinicians in rehabilitation most often responded "reasonable" in response to an accommodation (n = 24, reasonable: 80.20%), while those who worked in outpatient pediatrics selected "unreasonable" most often (n = 4, unreasonable: 13.51%). This preliminary data provides stakeholders information about accommodations, creating opportunities to support students with disabilities in their pursuit of becoming clinicians. This will help to better fulfill American Occupational Therapy Association's vision of inclusivity and equitability.